2019
DOI: 10.1186/s12888-019-2214-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower versus higher frequency of sessions in starting outpatient mental health care and the risk of a chronic course; a naturalistic cohort study

Abstract: Background An adequate frequency of treatment might be a prerequisite for a favorable outcome. Unfortunately, there is a diversity of factors that interfere with an adequate frequency of sessions. This occurs especially in the first phase of treatment, while the first phase seems vital for the rest of treatment. The aim of this naturalistic study was to explore the impact of the initial frequency of treatment sessions on treatment outcome in a diverse mental health care population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Moreover, the massed treatment leads to a faster reduction in PTSD symptoms. The findings that a higher session frequency is related to better outcomes are consistent with findings based on a meta-analysis on treatments for depression [ 22 ] and naturalistic studies across different diagnostic groups (e.g., depression, anxiety disorders, personality disorders) [ 23 , 24 ]. Furthermore, a RCT among depressive patients demonstrated that delivering treatment twice a week is more effective than delivering treatment only once a week (difference in effect size d = 0.55 [ 25 ]).…”
Section: Introductionsupporting
confidence: 83%
“…Moreover, the massed treatment leads to a faster reduction in PTSD symptoms. The findings that a higher session frequency is related to better outcomes are consistent with findings based on a meta-analysis on treatments for depression [ 22 ] and naturalistic studies across different diagnostic groups (e.g., depression, anxiety disorders, personality disorders) [ 23 , 24 ]. Furthermore, a RCT among depressive patients demonstrated that delivering treatment twice a week is more effective than delivering treatment only once a week (difference in effect size d = 0.55 [ 25 ]).…”
Section: Introductionsupporting
confidence: 83%
“…5 In an observational study, a higher session frequency was associated with improvement and recovery within the first three months of treatment. 6 However, a randomised trial on the direct effect of psychotherapy session frequency on depression is lacking. The original Beck manual for cognitive–behavioural therapy (CBT) for depression 7 prescribes that CBT should start twice weekly in the beginning of treatment, whereas interpersonal psychotherapy (IPT) should be delivered once a week, according to Klerman's manual.…”
mentioning
confidence: 99%
“…Higher session frequency in the first 3 months of treatment is associated with faster improvement and recovery (Tiemens et al, 2019). Further, patients randomized to receive twice-weekly sessions experienced greater depression reductions than those offered once-weekly therapy (Bruijniks et al, 2020).…”
Section: Treatment Need Not Occur Once-weeklymentioning
confidence: 93%